Municipal waste incinerators: air and biological monitoring of workers for exposure to particles, metals, and organic compounds. Issue 8 (25th July 2003) - Maître, A; Collot-Fertey, D; Anzivino, L; Marques, M; Hours, M; Stoklov, M
Abstract : Aims: To evaluate occupational exposure to toxic pollutants at municipal waste incinerators (MWIs). Methods: Twenty nine male subjects working near the furnaces in two MWIs, and 17 subjects not occupationally exposed to combustion generated pollutants were studied. Individual air samples were taken throughout the shift; urine samples were collected before and after. Stationary air samples were taken near potential sources of emission. Results: Occupational exposure did not result in the infringement of any occupational threshold limit value. Atmospheric exposure levels to particles and metals were 10–100 times higher in MWIs than at the control site. The main sources were cleaning operations for particles, and residue transfer and disposal operations for metals. MWI workers were not exposed to higher levels of polycyclic aromatic hydrocarbons than workers who are routinely in contact with vehicle exhaust. The air concentrations of volatile organic compounds and aldehydes were low and did not appear to pose any significant threat to human health. Only the measurement of chlorinated hydrocarbon levels would seem to be a reliable marker for the combustion of plastics. Urine metal levels were significantly higher at plant 1 than at plant 2 because of high levels of pollutants emanating from one old furnace. Conclusion: While biological monitoring is an easy way of acquiring data on long term personal exposure, air monitoring remains the only method that makes it possible to identify the primary sources of pollutant emission which need to be controlled if occupational exposure and environmental pollution are to be reduced.